ApoA-I Nanotherapy Rescues Postischemic Vascular Maladaptation by Modulating Endothelial Cell and Macrophage Phenotypes in Type 2 Diabetic Mice. Issue 1 (17th November 2022) - Babu, Mohan; Devi, Durga; Mäkinen, Petri; Örd, Tiit; Aavik, Einari; Kaikkonen, Minna; Ylä-Herttuala, Seppo
Abstract : Background: Diabetes is a major risk factor for peripheral arterial disease. Clinical and preclinical studies suggest an impaired collateral remodeling and angiogenesis in response to atherosclerotic arterial occlusion in diabetic conditions, although the underlying mechanisms are poorly understood. Objective: To clarify the cellular and molecular mechanisms underlying impaired postischemic adaptive vascular responses and to evaluate rHDL (reconstituted HDL)-ApoA-I nanotherapy to rescue the defect in type 2 diabetic mouse model of hindlimb ischemia. Methods and Results: Hindlimb ischemia was induced by unilateral femoral artery ligation. Collateral and capillary parameters together with blood flow recovery were analyzed from normoxic adductor and ischemic gastrocnemius muscles, respectively, at day 3 and 7 post-ligation. In response to femoral artery ligation, collateral lumen area was significantly reduced in normoxic adductor muscles. Distally, ischemic gastrocnemius muscles displayed impaired perfusion recovery and angiogenesis paralleled with persistent inflammation. Muscle-specific mRNA sequencing revealed differential expression of genes critical for smooth muscle proliferation and sprouting angiogenesis in normoxic adductor and ischemic gastrocnemius, respectively, at day 7 post-ligation. Genes typical for macrophage (Mϕ) subsets were differentially expressed across both muscle types. Cell-specific gene expression, flow cytometry, and immunohistochemistry revealed persistent IFN-I response gene upregulation in arterial endothelial cells, ECs and Mϕs from T2DM mice associated with impaired collateral remodeling, angiogenesis and perfusion recovery. Furthermore, rHDL nanotherapy rescued impaired collateral remodeling and angiogenesis through dampening EC and Mϕ inflammation in T2DM mice. Conclusions: Our results suggest that an impaired collateral remodeling and sprouting angiogenesis in T2DM mice is associated with persistent IFN-I response in ECs and Mϕs. Dampening persistent inflammation and skewing ECs and Mϕ phenotype toward less inflammatory ones using rHDL nanotherapy may serve as a potential therapeutic target for T2DM peripheral arterial disease.